Control of Flowering Time and Cold Response by a NAC-Domain Protein in Arabidopsis - Yoo, So Yeon (Public Library of Science, 2007)

(untitled)
BACKGROUND: Plants must integrate complex signals from environmental and endogenous cues to fine-tune the timing of flowering. Low temperature is one of the most common environmental stresses that affect flowering time; however, molecular mechanisms underlying the cold temperature regulation of flowering time are not fully understood. METHODOLOGY/PRINCIPAL FINDINGS: We report the identification of a novel regulator, LONG VEGETATIVE PHASE 1 (LOV1), that controls flowering time and cold response. An Arabidopsis mutant, long v egetative phase 1-1D (lov1-1D) showing the late-flowering phenotype, was isolated by activation tagging screening. Subsequent analyses demonstrated that the phenotype of the mutant resulted from the overexpression of a NAC-domain protein gene (At2g02450). Both gain- and loss-of-function alleles of LOV1 affected flowering time predominantly under long-day but not short-day conditions, suggesting that LOV1 may act within the photoperiod pathway. The expression of CONSTANS (CO), a floral promoter, was affected by LOV1 level, suggesting that LOV1 controls flowering time by negatively regulating CO expression. The epistatic relationship between CO and LOV1 was consistent with this proposed regulatory pathway. Physiological analyses to elucidate upstream signalling pathways revealed that LOV1 regulates the cold response in plants. Loss of LOV1 function resulted in hypersensitivity to cold temperature, whereas a gain-of-function allele conferred cold tolerance. The freezing tolerance was accompanied by upregulation of cold response genes, COLD-REGULATED 15A (COR15A) and COLD INDUCED 1 (KIN1) without affecting expression of the C-repeat-binding factor/dehydration responsive element-binding factor 1 (CBF/DREB1) family of genes. CONCLUSIONS: Our study shows that LOV1 functions as a floral repressor that negatively regulates CO expression under long-day conditions and acts as a common regulator of two intersecting pathways that regulate flowering time and the cold response, respectively. Our results suggest an overlapping pathway for controlling cold stress response and flowering time in plants.